Access to Schooling and Staying in School in Selected Sub‐Saharan African Countries1 . (17th December 2015) - Kuépié, Mathias; Shapiro, David; Tenikue, Michel
Abstract: This study jointly investigates factors driving the processes of accessing and staying in school in sub‐Saharan Africa. We explicitly account for the fact that staying in school or its converse, dropping out, is observed only among children who ever attend school. We use data from Demographic and Health Surveys from 12 countries. We find that access to school is typically lower for females, rural youth, and those from poorer households. Conditional on having ever attended school, these factors, as well as age in grade – an indicator of performance in school – typically help account for staying in school. We also find that keeping girls at school is very sensitive to school performance: girls with comparatively weak performance in school are more likely than their male counterparts to drop out of school, while girls who do relatively well in school are more likely to remain in school than boys, other things being equal.